Comparação do padrão respiratório e do movimento toracoabdominal de idosos saudáveis em diferentes faixas etárias - Leticia Silva Gabriel (2015)
Introduction: The respiratory system changes with aging in healthy subjects.Changes in the lungs, chest wall, respiratory muscles and also in the respiratory drive there are connected to senility of the respiratory tract. There is no study in the literature evaluating the breathing pattern and the thoracoabdominal motion in elderly people from different age groups in different positions. Objectives: To evaluate breathing pattern and thoracoabdominal motion in the sitting, supine position 0° and with a trunk inclination of 45°, in healthy elderly individuals from different age groups (60-69, 70-79, >80 years old). Besides, to identify if there is an increase in the end-expiratory volume of the chest wall with the advance of age in the three positions. Methods: We studied 28 healthy elderly individuals of both sexes (71.46 ± 6.57 years, body mass index 26.21 ± 2.99) and with normal pulmonary function test. The following variables were analyzed: tidal volume of the chest wall (Vcw); percentages of contribution of the pulmonary rib cage (RC), RC abdominal rib cage and the abdomen; end-expiratory volume of the chest wall (Veecw); end-inspiratory volume of the chest wall (Veicw); minute ventilation (VE); medium inspiratory flow; percentage of inspiratory time to the total time; respiratory rate; phase angle and the ratio of total phase. Subjects were analyzed in three positions: sitting and supine position - zero degree and with a slope of 45 degrees, at rest for five minutes. Were used for statistical analysis: the analysis of variance (ANOVA) mixed factorial design with repeated measures on plots and subplots 3x3 (3 age groups and 3 positions). The post hoc comparisons were made using the Bonferroni test for multiple comparisons considering the three positions (delta sitting-inclined; delta sitting-supine; delta inclined-supine). Results:The main results observed in relation to the breathing pattern variables were: there was a decreased in the contribution of pulmonary rib cage (average of 19% - in all age groups), a decreased in the contribution of the abdominal rib cage (average of 11% - in the three age groups which was associated with an increased in the abdominal contribution. (average of 30% - in all age groups) in changing from the sitting position to the supine position 0°. Regarding Veecw and Veicw in the range of 60-69 years and above 80 years there was a significant decrease between sitting and supine position 0° (average of 3% - in both age groups) and an increase between inclination of 45° and supine position 0° (average of 3% - in both age groups). Only in the elderly of 60-69 years there was a reduction on the Vcw(21%) and on the VE (18%) between the sitting and supine position 0°. In relation to thoracoabdominal motion no consistent changes were observed. Age doesn´t seems to affect any of the breathing pattern variables nor the thoracoabdominal motion ones. and. Conclusion: The results suggest that breathing pattern and thoracoabdominal motion were influenced by the body position, but not by age. The largest tidal volume was observed in the sitting position